Role of Music as a Therapeutic Measure in Women’s Health - Sivanandan , Anagha (International Research Journal of Ayurveda & Yoga, 2022)
Background: Music is such an art form that conveys emotions and perceptions even without using a language. The research activities focusing on the effects of art forms on health and well-being has been evidently increasing over the past two decades. Music therapy is a widely accepted and popular form for improving health through arts. Studies have shown that women being more sensitive and sentimental can be influenced more easily by music. Materials and Methods: Review of relevant literature from modern medical science, Ayurvedic classics, text books of Indian Musicology, previous research works, articles published in peer reviewed journals and other genuine sources of internet. Results: Music plays a significant role in improving the health and wellbeing of a female both in preventive and therapeutic aspects. Discussion: Music being the product of Akasha and Vayu Mahabhuta is capable of controlling the bodily Vata Dosha. Ayurveda consider music as a means to tackle Pitta Dosha mainly. Previous research works have shown the effect of Indian classical music on gastric and allied secretions in digestive system where there is a major role for Pitta Dosha. The coordinated activity of Hypothalamo- Pituitary- Ovarian Axis (HPO Axis) is responsible for normal menstrual and reproductive mechanism in females where Vata and Pitta are having the main roles. So music can play an appreciable role in maintaining the normal functions in HPO axis.